Achievements of UNCTAD-1 (1964) and UNCTAD-11 (1968) In the Field of Shipping and Invisibles: With Full Documentation - Singh, Nagendra; United Nations Conference on Trade and Development (New Delhi: S. Chand & Co., 1969)
This monograph which concerns itself exclusively with invisibles including shipping, insurance and tourism, is a welcome addition to the literature dealing with the economic growth and development of the developing countries. Furthermore, information relating to international non-merchandise trade, apart from financial items, is by no means as complete, comparable or reliable as that relating to merchandise trade; this publication attempts to fill the gap.
Foreword by Singh Shri Dinesh- President of UNCTAD-11.
Including index: p. [575]-576.
ne 21/03/2018
Loan
Keywords: Shipping